ACCURACY OF MULTIPHASE HELICAL TOMOGRAPHY IN DETECTION AND CHARACTERISATION OF SUSPECTED RENAL MASSES USING HISTOPATHOLOGICAL FINDINGS AS GOLD STANDARD - Siddiqui, Tariq Saeed; Tariq, Asima; Rehman, Bushra; Siddiqui, Tahir Saeed; Asim, Aisha (Journal of Ayub Medical College Abbottabad, 2010)
Background: The introduction of multiphase helical computed tomography has created many important advances in the detection and characterisation of renal masses. Renal cell carcinoma (RCC) is the seventh most common cancer and makes up 80-85% of all primary renal cancer in adults. If it is found and treated early, the chances of survival from kidney cancer are high. This cross-sectional comparative was carried out at department of CMH/MH Rawalpindi from 1st February 2007 to 25 March 2008 to evaluate accuracy of multiphase helical tomography in detection and characterisation of suspected renal masses using histopathological findings as gold standard. Methods: Thirty patients with suspicion of having renal masses were scanned with multiphase CT scanning and 5 mm thick contiguous section were obtained from kidneys before and after injection of intravenous contrast material. The corticomedullary phase images were obtained after a delay of 25 seconds and nephrographic phase images, after a delay of 120 seconds after initiation of contrast medium injection. The numbers of lesions detected in all three phases were determined. The mass was then characterised by evaluation of its features and by its degree of contrast enhancement. Results of CT scan were compared with histopathology. Results: At review of unenhanced, corticomedullary and nephrographic phase images, 26, 29 and 30 lesions, respectively, were identified. One malignant lesion was not identified and 3 malignant lesions falsely appeared benign in the corticomedullary phase. All lesions were detected in the nephrographic phase and only 1 malignant lesion falsely appeared benign. The corticomedullary phase had a sensitivity of 86.2% and nephrographic phase 96.6% in malignant lesion detection. Conclusion: Enhancement of renal neoplasm is time dependent and is better in nephrographic phase. Small, hypovascular tumours and those placed in medulla may be missed or inadequately characterised if nephrographic phase scanning is not done. Keywords: Computed tomography, renal masses, corticomedullary phase, nephrographic phase